Answer:
The value to the given expression is x=-2
Step-by-step explanation:
Given equation is
[tex]\frac{1}{2}(8x-4)-5=-3(x+4)-9[/tex]
To simplify the given equation
[tex]\frac{1}{2}(8x-4)-5=-3(x+4)-9[/tex] ( By using the distributive property )
[tex]\frac{(8x-4)}{2}-5=-3x-12-9[/tex]
[tex]8x-14=2(-3x-21)[/tex] ( adding like terms )
[tex]8x-14=2(-3x-21)[/tex]
[tex]8x-14=-6x-42[/tex] ( By Using the distributive property )
[tex]8x-14+6x+42=0[/tex] ( combine terms to simplify )
[tex]14x+28=0[/tex]( adding like terms )
[tex]14x=-28[/tex]
[tex]x=\frac{-28}{14}[/tex]
[tex]x=-2[/tex]
Therefore x=-2
The value to the given expression is x=-2